Biochemical and molecular responses of the freshwater snail Pila sp. to environmental pollutants, abiotic, and biotic stressors - Panda, Falguni; Pati, Samar Gourav; Das, Kajari; Samanta, Luna; Sahoo, Dipak Kumar; Paital, Biswaranjan (Frontiers in Environmental Science, 2022)
The semi-sessile, ectothermic, amphibious mollusc Pila globosa receives less attention for studying its environmental aspects. Its ecological role, ecotoxic and physiological responses to environmental factors including pollution and during dormant periods such as hibernation and estivation to understand key information about many cellular metabolic events need to be revealed. We reviewed the ecotoxic and physiological responses of P. globosa to various abiotic and biotic stressors such as heavy metals, organophosphorous, carbamate and butachlor in relation its adaptation to energy expenditure, fat metabolism in the dormant period, desiccation, etc. The responses analysed in terms of oxidative stress, respiratory and antioxidant enzymes, carbohydrate metabolism and activities of neurotransmitter enzymes such as acetylcholinesterase to better understand the connection between environmental factors and metabolic events in P. globosa. Articles published in the English language from 1952 to July of 2022 in PubMed, Google search engine and AGRICOLA that describes any of the above-mentioned search terms in P. globosa were included in the review article. Articles not containing any of the above terms were excluded. The 41 results were found in PubMed and 10 results from AGRICOLA and about 80 filtered articles from Google, totaling about 80 articles published until July 2022 were included in this review. The varied enzymatic activities observed in this organism under the exposure to various chemicals imply their possible use as biomarkers of eco-toxicological studies in freshwater and grassland ecosystems, for example, alleviated body carbohydrate and protein contents are up to 32 and 37% during aestivation and hibernation, respectively. Similarly, activities of enzymes such as adenosine monophosphate deaminase, adenosine deaminase, succinic dehydrogenase, cytochrome-c-oxidase, and glutamate dehydrogenase are downregulated by 75.5, 62.6, 54, 59, and 62%, respectively, during above inactive periods. Acetylcholinesterase enzyme is found to be the most susceptible enzyme to be downregulated by 225, 130, 64, 198, 96.08% in this snail under exposure to environmental pollutants such as phorate (30 mg/L), formothion (37.5 mg/L), trichlorfon (2.5 mg/L), aldicarb (120 mg/L) and butachlor (100 µ moles), respectively. In conclusion, P. globosa can serve as a reliable ectothermic model for comparative ecotoxicological studies in grassland and freshwater environmental monitoring.